Bioethics in Experimentation with Human Beings - Esquivel, José Miguel (2002)
In the practice of medicine, knowledge is used with a specific, concrete purpose: to prevent, alleviate or cure the ailments of a sick human being. For this purpose, one has to take and use knowledge of philosophy, anatomy, biochemistry, microbiology, genetics, nuclear medicine, immunology, pathology, etc., but also from the physics of chemistry, etc., and even more of psychology, of society and also of ethics. What should be emphasized is the global vision, the holistic conception of the patient. This raises a progressive subdivision and superspecialization of medical knowledge, generating problems of an epistemological-didactic order and even of an ethical order.